Assessing polar bear (Ursus maritimus) population structure in the Hudson Bay region using SNPs. Issue 23 (28th October 2016) - Viengkone, Michelle; Derocher, Andrew Edward; Richardson, Evan Shaun; Malenfant, René Michael; Miller, Joshua Moses; Obbard, Martyn E.; Dyck, Markus G.; Lunn, Nick J.; Sahanatien, Vicki; Davis, Corey S.
Abstract: Defining subpopulations using genetics has traditionally used data from microsatellite markers to investigate population structure; however, single‐nucleotide polymorphisms (SNPs) have emerged as a tool for detection of fine‐scale structure. In Hudson Bay, Canada, three polar bear ( Ursus maritimus ) subpopulations (Foxe Basin (FB), Southern Hudson Bay (SH), and Western Hudson Bay (WH)) have been delineated based on mark–recapture studies, radiotelemetry and satellite telemetry, return of marked animals in the subsistence harvest, and population genetics using microsatellites. We used SNPs to detect fine‐scale population structure in polar bears from the Hudson Bay region and compared our results to the current designations using 414 individuals genotyped at 2, 603 SNPs. Analyses based on discriminant analysis of principal components (DAPC) and STRUCTURE support the presence of four genetic clusters: (i) Western—including individuals sampled in WH, SH (excluding Akimiski Island in James Bay), and southern FB (south of Southampton Island); (ii) Northern—individuals sampled in northern FB (Baffin Island) and Davis Strait (DS) (Labrador coast); (iii) Southeast—individuals from SH (Akimiski Island in James Bay); and (iv) Northeast—individuals from DS (Baffin Island). Population structure differed from microsatellite studies and current management designations demonstrating the value of using SNPs for fine‐scale population delineation in polar bears. Abstract : Using SNPs, we investigate fine‐scale population structure in polar bears of the Hudson Bay region of Canada and compare these findings to subpopulation designations. Based on 414 samples and 2, 603 SNPs, we conclude there are four genetic clusters that differ from current management.